2016
DOI: 10.1037/pas0000164
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Strengths Scale for individuals with mental health issues.

Abstract: Using their strengths and virtues enables individuals to build resilience and alleviate mental health issues. However, most existing instruments for measuring strengths are too lengthy to provide effective assessment for clinical screening. A brief instrument with good factorial and ecological validity is needed to measure strengths, especially among individuals with mental health issues. In this study, the authors developed a brief inventory, the Brief Strengths Scale-12 (BSS-12), to assess 3 strengths: Tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 82 publications
3
22
0
Order By: Relevance
“…A reasonable assumption is that the difference may be caused by the variations in the demographic variables (e.g., gender, age, education, and marriage) between the student and community samples. In a previous study, the 12-item scale was validated through an undergraduate sample via CFA (Ho et al 2016), which comprised highly educated, unmarried, and young persons. The currently used sample is obviously more diverse and complex.…”
Section: Cfas Results and Reliabilitymentioning
confidence: 99%
See 4 more Smart Citations
“…A reasonable assumption is that the difference may be caused by the variations in the demographic variables (e.g., gender, age, education, and marriage) between the student and community samples. In a previous study, the 12-item scale was validated through an undergraduate sample via CFA (Ho et al 2016), which comprised highly educated, unmarried, and young persons. The currently used sample is obviously more diverse and complex.…”
Section: Cfas Results and Reliabilitymentioning
confidence: 99%
“…Education is a long-term and systematic project; only an extensive period of longitudinal study can provide direct evidence to verify whether education can change an individual's strengths and virtues. More recently, Duan (2016) suggested that mindfulness-based training may be helpful in cultivating these strengths. Although such empirical intervention research is non-existent, many schools have started to develop character education programs (Bernard and Walton 2011;White and Waters 2015), which can provide evidence for future studies.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations